2019
DOI: 10.1111/zph.12664
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus sciuri peritonitis in a patient on peritoneal dialysis

Abstract: An 82-year-old male with end-stage renal disease on peritoneal dialysis presented to the emergency department with 3 weeks of progressive lower abdominal pain. He had experienced intermittent pain during his daily peritoneal dialysis sessions. The pain became persistent and severe the morning of admission. On initial evaluation, his temperature was 37.2°C, blood pressure 148/90 mmHg, heart rate 88 beats per minute, respiratory rate of 17 breaths per minute and arterial oxygen saturation of 98% on room air. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…S. aureus is a recognized foodborne pathogen [ 9 ]. Other Staphylococcus spp., such as S. epidermidis , S. intermedius , S. saprophyticus , S. hyicus , S. pasteuri , S. cohnii , S. warneri , S. lugdunensis , S. sciuri , and S. simulans , can cause infections in humans [ 21 , 68 , 69 , 70 , 71 , 72 , 73 ]. Some of these staphylococci were isolated in the present work ( S. aureus , S. epidermidis , S. saprophyticus , S. hyicus , S. pasteuri , S. cohnii , S. warneri , S. sciuri , and S. simulans ).…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is a recognized foodborne pathogen [ 9 ]. Other Staphylococcus spp., such as S. epidermidis , S. intermedius , S. saprophyticus , S. hyicus , S. pasteuri , S. cohnii , S. warneri , S. lugdunensis , S. sciuri , and S. simulans , can cause infections in humans [ 21 , 68 , 69 , 70 , 71 , 72 , 73 ]. Some of these staphylococci were isolated in the present work ( S. aureus , S. epidermidis , S. saprophyticus , S. hyicus , S. pasteuri , S. cohnii , S. warneri , S. sciuri , and S. simulans ).…”
Section: Discussionmentioning
confidence: 99%
“…The coagulase-negative species S. sciuri is an opportunistic pathogen, typically found in many habitats, including animals, humans, and the environment [40][41][42][43]. S. sciuri is an important human pathogen responsible for endocarditis, peritonitis, urinary tract infections, wound/skin infections, and septic shock [43][44][45][46][47]. Infections of S. sciuri in human hospitals are emerging and increasing in several countries [48][49][50][51], which may result from the high adaptation capacity to the environment [52].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of MRSS in this study also had an MDR phenotype which is rarely reported; MDR staphylococci are mainly S. aureus [77][78][79][80]. MRSS carrying multiple AMR genes might threaten animal and human health because this pathogen is capable of causing a variety of diseases and transmit AMR genes to other staphylococci [43][44][45][46][47][53][54][55]. Interspecies horizontal gene transfer from S. sciuri to others could occur through many mechanisms, but bacteriophage has been shown to be one such mechanism [81].…”
Section: Discussionmentioning
confidence: 99%
“…S. sciuri has also been found to be associated with infections in bovine ( Vanderhaeghen et al, 2013 ; Nemeghaire et al, 2014b ; Qu et al, 2019 ), poultry ( Lu et al, 2020 ), and horses ( Beims et al, 2016 ). Additionally, S. sciuri isolated from hospital environment ( Dakic et al, 2005 ) has been implicated in case reports of peritonitis ( Meservey et al, 2020 ), amputations ( Coimbra et al, 2011 ), and other complications.…”
Section: Introductionmentioning
confidence: 99%